Hungarian Monitoring, 9 February 1990 . [Magyar rádiófigyelő], 1990. február 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Baker-Gorbachev-Shevardnadze talks - Kohl and Genscher's visit to Moscow - The future of Germany: reprivatization in the GDR - Bonn government extends loan to USSR to purchase foodstuffs - Temporary legislative body created in Romania - Establishment of Czechoslovak-Israeli relations - Yugoslavia: Kosovo crisis Domestic Affairs: - Hungarian-Vatican relations - Ferenc Glatz in Vienna - Gyula Horn's Canadian talks - József Antall holds press conference on his experiences in the States - Election: election programs, the church calls for electoral participation - Hungary unilaterally renounces 1979 agreement signed with Romania that excludes the possibility of dual nationality - László Tőkés's Budapest schedule and press conference Economy: - Japanese bank extends 5 billion yen loan to the Hungarian National Bank Külpolitika: - Baker-Gorbacsov-Sevardnadze tárgyalások - Kohl és Genscher moszkvai útja - Németország jövője; reprivatizálás az NDK-ban - A bonni kormány hitelt nyújt a SZU-nak élelmiszer vásárlásra - Az átmeneti törvényhozó testület létrehozása Romániában - A csehszlovák-izraeli kapcsolatok alakulása - Jugoszlávia: a koszovói válság Belpolitika: - Magyar - Vatikáni kapcsolatok - Glatz Ferenc Bécsben - Horn Gyula kanadai tárgyalásai - Antall József sajtótájékoztatója amerikai tapasztalatairól - Választás: választási műsorok, az egyházak felhívása a szavazáson való részvételre - Magyarország egyoldalúan felmondta a kettős állampolgárság kizárásáról 1979-ben Romániával megkötött egyezményt - Tőkés László budapesti programja és sajtótájékoztató Gazdaság: - Egy japán bank 5 milliárd yenes hitelt nyújt a MNB-nak